NEONATAL SEIZURES: ETIOLOGY, TREATMENT AND PROGNOSIS - Misanovix, Verica; Hodžić, Edna; Terzić, Sabina; Vukas-Salihbegović, Emina; Ključić, Amila (Sanamed, 2022)
Introduction: Seizures are one of the most common pathologies in newborns.  Their incidence is 1.5–3.5/1000 for term infants and 10–130/1000 for preterms. The most common causes of seizures in term infants are hypoxic-ischemic encephalopathy (HIE), cerebrovascular insult (CVI), cerebral malformations (CM), and metabolic disorders. For preterm infants: intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL) and infections. Clinical characteristics are diverse and subtle, and subclinical forms are common. The drug of the first choice is phenobarbitone. Newborns with seizures are more prone to developing neurological disturbances such as epilepsy and cerebral palsy.Methods: This is a clinical, observational research, one-year, retrospective, cross-sectional study conducted in the Department of neonatal intensive care and neonatology of the Clinic of Pediatrics  KCUS. The study included 43 newborns who met the inclusion criteria.Results: We found that 7.19% of hospitalized newborns had seizures. A number of seizures were recorded in the group of term infants with an earlier time of seizures. The most common etiological causes were: HIE, IVH, infections, and CM. There was a frequent occurrence of metabolic disorders such as acidosis, blood sugar, and mineral (Ca, K, Na, and Mg) disorders. The median of the first day of onset of seizures in full-term infants is on the fourth day, while in premature infants it is on the sixth day of life. Phenobarbitone was mainly used to stop seizures, with great success. Overall mortality in children with seizures was 37.21%.Conclusions: Seizures are common in newborns, which, depending on the etiological cause, increase mortality, especially in preterm infants. Seizures in term infants occur earlier than in premature infants. The most common etiology of seizures in term infants are infections, hypoxemic-ischemic encephalopathy, intracranial hemorrhage, cerebral malformations, and cerebrovascular insult. In premature infants these are hypoxemic-ischemic encephalopathy, intracranial bleeding, and infections. In the initial treatment of neonatal convulsions, phenobarbitone is most often used, which has proven to be successful in the majority of cases.
Keywords: neonatal seizures; etiology; treatment; prognosis; mortality